Genomic and epidemiological surveillance of SARS-CoV-2 variants during the pre-mass vaccination period in Botucatu, Brazil - da Costa, Felipe Allan da Silva [UNESP]; Assato, Patricia Akemi; Tasca, Karen Ingrid [UNESP]; de Moraes, Leonardo Nazário [UNESP]; dos Santos Figueiredo, Drielle Baptista [UNESP]; Ribeiro, Gabriela; Lima, Alex Ranieri Jerônimo; Sampaio, Sandra Coccuzzo; Elias Sabbaga, Maria Carolina Quartim Barbosa; Fortaleza, Carlos Magno Castelo Branco [UNESP]; de Souza-Neto, Jayme Augusto; Grotto, Rejane Maria Tommasini [UNESP] (Springer Nature, 2025)
The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has caused an unprecedented pandemic in human history. To date, more than 6.5 million lives have been lost to COVID-19 (coronavirus disease 2019). Following widespread efforts for COVID-19 vaccination in Brazil, there has been a drastic reduction in COVID-19 deaths, which was particularly evident in the city of Botucatu, SP, Brazil, after a campaign to a mass vaccination. Our objective was to assess the temporal and epidemiological spread of variants of concern (VOC) of SARS-CoV-2 in the four weeks preceding the massive vaccination campaign in the municipality. After randomizing 400 samples, Next-Generation Sequencing was used to produce sequences and determine the variants. Among high-quality sequences, 98.4% belonged to the VOC Gamma, with P.1 and P.1.14 being the most prevalent lineages. P.1 was more frequent in both men and women, and in younger individuals and adults (0–59 years) compared to P.1.14. There was no correlation between the variants and the presence of comorbidities or between them and moderate to severe clinical cases of COVID-19 or death. However, P.1 was more frequent than P.1.14 in people with mild forms of the disease and in those who exhibited symptoms. In the phylogenetic analyses, a small cluster of 9 P.1.14 samples containing mutations in ORF1a: M584V and A3620V was observed, which had not been found in any Gamma sequences to date. The importance of genomic surveillance of SARS-CoV-2 is evident in assisting public health decision-making and the management of COVID-19 and other diseases.
Keywords: COVID-19 vaccination; Genomic mutation tracking; Genomic surveillance; SARS-CoV-2 variants; Vaccination impact